2018
DOI: 10.1186/s12909-018-1370-4
|View full text |Cite
|
Sign up to set email alerts
|

Ready to run the wards? – A descriptive follow-up study assessing future doctors’ clinical skills

Abstract: BackgroundRecent studies have shown that clinical tasks only represent a small percentage in the scope of final-year medical students’ activities and often lack sufficient supervision. It appears that final-year medical students are frequently deployed to perform “routine tasks” and show deficits in the performance of more complex activities. This study aimed to evaluate final-year students’ clinical performance in multiple impromptu clinical scenarios using video-based assessment.MethodsWe assessed final-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…The move towards competency based medical education (CBME) globally had highlighted this need and also the challenges inherent to ensuring achievement of these competencies [1]. Wide variability in procedural skills have been observed among junior doctors even after adoption of CBME raising questions about their readiness to undertake roles expected of them [2]. Many studies have confirmed the positive significant benefit of adding multimedia-based training to traditional text-based training [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The move towards competency based medical education (CBME) globally had highlighted this need and also the challenges inherent to ensuring achievement of these competencies [1]. Wide variability in procedural skills have been observed among junior doctors even after adoption of CBME raising questions about their readiness to undertake roles expected of them [2]. Many studies have confirmed the positive significant benefit of adding multimedia-based training to traditional text-based training [7].…”
Section: Discussionmentioning
confidence: 99%
“…Wide variation is observed in skills in performing common bedside clinical procedure of male bladder catheterisation among final phase MBBS students trained through conventional training and assessment [1,2]. Conventional teaching and learning methods may not allow assurance of achievement of competencies in the Indian Medical Graduate IMG.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in other countries have revealed that the majority of newly graduated physicians, appointed to provide medical service in rural areas, due to lack of clinical experience, are not self-confident to provide appropriate medical care to patients (Goldacre et al 2003;Karakus and S¸enyer 2014;Gazibara et al 2015;Bugaj et al 2018;van der Voort et al 2019). This is particularly true for the Greek young physicians.…”
Section: Obligatory Service In a Rural Area (District Doctor)mentioning
confidence: 99%
“…Wide variation is observed in skills in performing common bedside clinical procedure of male bladder catheterization among final phase MBBS students trained through conventional training and assessment. 1,2 Conventional teaching and learning methods may not allow assurance of achievement of competencies in the Indian Medical Graduate. 1 Introduction of structured training methods could offer a reliable method of facilitation of learning and assured skill acquisition.…”
Section: Introductionmentioning
confidence: 99%